Pelatihan Refresher Training Aerodrome Control Tower untuk Personil Air Traffic Control Tentara Nasional Indonesia Angkatan Udara - Imam Sonhaji; Djoko Jatmoko; Lina Rosmayanti; Nunuk Praptiningsih; Elfi Amir (Jurnal Pengabdian Kepada Masyarakat (JPKM) Langit Biru, 2022)
All Air Traffic Controller personnel have an obligation to maintain their competence, one of which is by participating in Refresher Training at least once every 3 (three) years, the problem that is that not all Air Traffic Controller personnel from the Indonesian Air Force get the opportunity to take part in Refresher Training. PKM for PPI Curug lecturers through Refresher Training Aerodrome Control Tower Training are carried out offline or face to face. The result is that this refreshing training can provide knowledge and competence for ATC personnel from the Indonesian Air Force to continue to be the leading pioneers in maintaining aviation safety in Indonesia